2017
DOI: 10.3390/toxins9090274
|View full text |Cite
|
Sign up to set email alerts
|

Cobra Venom Factor and Ketoprofen Abolish the Antitumor Effect of Nerve Growth Factor from Cobra Venom

Abstract: We showed recently that nerve growth factor (NGF) from cobra venom inhibited the growth of Ehrlich ascites carcinoma (EAC) inoculated subcutaneously in mice. Here, we studied the influence of anti-complementary cobra venom factor (CVF) and the non-steroidal anti-inflammatory drug ketoprofen on the antitumor NGF effect, as well as on NGF-induced changes in EAC histological patterns, the activity of lactate and succinate dehydrogenases in tumor cells and the serum level of some cytokines. NGF, CVF and ketoprofen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[40,41] Ibuprofen can be prescribed for various diseases, like arthritis, osteoarthritis, and musculoskeletal disorders. [42] While the effects of NSAIDs include the inhibition of cyclooxygenase (COX) enzyme activity; [43][44][45] it has been demonstrated that inhibition of COX-2 has serious side effects such as gastrointestinal injury, as well as kidney and liver damage and cardiac arrest. [46,47] In addition, treatments of bacterial infections with ibuprofen speed the recovery process from vaginal infections, cellulitis, or acne.…”
Section: Introductionmentioning
confidence: 99%
“…[40,41] Ibuprofen can be prescribed for various diseases, like arthritis, osteoarthritis, and musculoskeletal disorders. [42] While the effects of NSAIDs include the inhibition of cyclooxygenase (COX) enzyme activity; [43][44][45] it has been demonstrated that inhibition of COX-2 has serious side effects such as gastrointestinal injury, as well as kidney and liver damage and cardiac arrest. [46,47] In addition, treatments of bacterial infections with ibuprofen speed the recovery process from vaginal infections, cellulitis, or acne.…”
Section: Introductionmentioning
confidence: 99%
“…Nerve growth factor (NGF) is among the least abundant toxins in snake venom [ 191 , 192 , 193 , 194 , 195 , 196 ]. Nevertheless, snake venom is considered a rich active source of this peptide [ 197 , 198 ].…”
Section: Venom Constituents and Biomedical Applicationsmentioning
confidence: 99%
“…First is the tropomyosin kinase receptor A (TrkA), with high and specific affinity [ 194 , 208 ], triggers the MAPK, ERK, and PI3K/AKT cytosolic/endosomal pathways [ 197 , 208 ], leading to proliferation arrest and the induction of differentiation in neuronal cells [ 207 ]. Second is the p75 pan-NT receptor (p75NTR) [ 194 , 197 ], with similar affinity but not specificity, is linked to cell apoptosis and growth arrest via the MAPK c-Jun N-terminal kinase pathways [ 209 ]. Interestingly, both NGF receptors have been observed to be expressed in tumors in the nervous system and are especially prevalent in breast cancer [ 198 ].…”
Section: Venom Constituents and Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work suggests that the antitumor effect of nerve growth factor in vivo depends critically on the normal status of the immune system. The nerve growth factor antitumor mechanism may cause an increase in lymphocytic infiltration in the tumor, a rise in the levels of IL-1β and TNF-α in the serum of tumor-bearing mice, and an increase in aerobic glycolysis [ 11 ]. Sales et al [ 12 ] questioned whether inhibitors of snake venom phospholipases A2 can lead to new insights into anti-inflammatory therapy in humans.…”
mentioning
confidence: 99%